A importância da família, para o processo de desenvolvimento do aluno no âmbito escolar - LUZ, Tamires da Silva (2018)
This course completion work addresses the topic of the importance of the family, for the development process of the student in the school environment. The main objective of this article is to understand the importance of family accompaniment in the educational life of children and adolescents within the school, so that everyone perceives the real need for their participation in keeping this student in the institution. As much the school as the family, together they can contribute to the formation of the individual, fact that led me to question: How can the family contribute to the improvement of learning in school education? What policies and strategies are defined by specialized literature to strengthen this relationship? The authors used such authors as Carvalho (2006), Cortella (2017), Fernandes (2013), and others. The methodology used was the bibliographical research, making possible the use of books, thesis articles and others. It was clear from the research that family support strengthens the construction of identity and the full development of children and adolescents. In the midst of so many conflicts and disorders, the school imposes itself to fulfill its social role and intervene in order not to multiply children and adolescents with depression or emotional traumas for reasons related to their parents' absence.